2018
DOI: 10.1101/418517
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heat-shock inducible CRISPR/Cas9 system generates heritable mutations in rice

Abstract: Transient expression of CRISPR/Cas9 is an effective approach for limiting its activities and improving its precision in genome editing. Here, we describe the heat-shock inducible CRISPR/Cas9 system for controlled genome editing, and demonstrate its efficiency in the model crop, rice. Using a soybean heatshock protein gene promoter and the rice U3 promoter to express Cas9 and sgRNA, respectively, we developed the heat-shock (HS) inducible CRISPR/Cas9 system, and tested its efficacy in targeted mutagenesis. Two … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 78 publications
(71 reference statements)
1
5
0
Order By: Relevance
“…Another interesting result of this study is the low targeting efficiency of HS-inducible Cas9 compared to constitutive Cas9 (Table 1 ). This finding was also appreciated by Nandy et al 36 , who compared the relative expressions of HS inducible- versus constitutive-Cas9 and found that the latter was 800 times more expressed than the former. The low expression level of inducible Cas9 can be partially balanced by its higher enzymatic activity at the high temperature used during the induction step, close to 40°C 37 .…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Another interesting result of this study is the low targeting efficiency of HS-inducible Cas9 compared to constitutive Cas9 (Table 1 ). This finding was also appreciated by Nandy et al 36 , who compared the relative expressions of HS inducible- versus constitutive-Cas9 and found that the latter was 800 times more expressed than the former. The low expression level of inducible Cas9 can be partially balanced by its higher enzymatic activity at the high temperature used during the induction step, close to 40°C 37 .…”
Section: Discussionsupporting
confidence: 58%
“…A basal expression of Cas9 (not yet induced by the treatment) was likely responsible for the DNA cleavage at CTS (between the third and the fourth nucleotide from the PAM site) with the outcome of some small deletions. Nandy and colleagues 36 , who applied heat‐shock-inducible CRISPR/Cas9 system in rice, detected a rate of basal targeted mutagenesis (before HS) around 16% (two out of 12 lines showed editing in one target site; 1 out of 6 lines in a second target site). This was quite unexpected because when used to drive expression of recombinase enzymes, the soybean heat-shock promoter proved to be tightly regulated by heat treatment 15 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…However, one major limitation of genome editing is the off-target mutations that are caused by Cas9 in transgenic plants. This limitation has been overcome to a considerable extent by the advent of stress-inducible CRISPR/Cas9 technique which reduces the rate of off-target mutations to negligible levels [112]. Thus, we can consider stressinducible CRISPR/Cas as a promising tool for precise and efficient genome editing in crop plants for numerous traits, including abiotic stress tolerance.…”
Section: Strategies To Combat Abiotic Stresses In Plantsmentioning
confidence: 99%
“…Adaptations to transformation vectors are typically used to increase genome editing efficiency, such as using different constitutive or germline‐specific promoters to control Cas9 expression or optimization of other regulatory sequences such as terminators, introns, or Pol III promoters that drive gRNA expression (Feng et al., 2018; Mao et al., 2016; Ordon et al., 2020; Tsutsui & Higashiyama, 2017; Wang et al., 2015; Yan et al., 2015). In addition to optimizing transformation vectors, mutagenesis efficiency can be increased by applying small molecules in mammalian cells (Yu et al., 2015) or applying heat in a variety of organisms (Greiner et al., 2017; LeBlanc et al., 2018; Li et al., 2021; Milner, Craze, Hope, & Wallington, 2020; Moreno‐Mateos et al., 2017; Nandy, Pathak, Zhao, & Srivastava, 2019; Vu et al., 2020; Xiang, Zhang, An, Cheng, & Wang, 2017). Although heat treatment can induce genome editing efficiency in plants, most published experimental setups make use of dedicated growth chambers to apply the heat treatment (An et al., 2020; Kurokawa et al., 2021; LeBlanc et al., 2018; Li et al., 2021; Milner et al., 2020; Nandy et al., 2019; Vu et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to optimizing transformation vectors, mutagenesis efficiency can be increased by applying small molecules in mammalian cells (Yu et al., 2015) or applying heat in a variety of organisms (Greiner et al., 2017; LeBlanc et al., 2018; Li et al., 2021; Milner, Craze, Hope, & Wallington, 2020; Moreno‐Mateos et al., 2017; Nandy, Pathak, Zhao, & Srivastava, 2019; Vu et al., 2020; Xiang, Zhang, An, Cheng, & Wang, 2017). Although heat treatment can induce genome editing efficiency in plants, most published experimental setups make use of dedicated growth chambers to apply the heat treatment (An et al., 2020; Kurokawa et al., 2021; LeBlanc et al., 2018; Li et al., 2021; Milner et al., 2020; Nandy et al., 2019; Vu et al., 2020). Such chambers might not be regularly available to a wide range of laboratories, and are notorious for temperature fluctuations.…”
Section: Introductionmentioning
confidence: 99%